2020
DOI: 10.1186/s12866-020-02007-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of mucoid to non-mucoid switch among carbapenemase-producing Klebsiella pneumoniae

Abstract: Background Klebsiella pneumoniae is a leading cause of intractable hospital-acquired multidrug-resistant infections and carbapenemase-producing K. pneumoniae (CPKp) are particularly feared. Most of the clinical isolates produce capsule as a major virulence factor. Recombination events at the capsule locus are frequent and responsible for capsule diversity within Klebsiella spp. Capsule diversity may also occur within clonal bacterial populations generating differences in colony aspect. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…This sample resulted in growth of mucoid and non-mucoid colonies of Klebsiella with different meropenem MICs. This phenomenon is well described by Chiarelli et al (2020). As this strain was detected in all seven laboratories on all except one agar plate (Table 5), it is therefore very unlikely that this has influenced the interpretation of the growth on these plates.…”
Section: Discussionsupporting
confidence: 68%
“…This sample resulted in growth of mucoid and non-mucoid colonies of Klebsiella with different meropenem MICs. This phenomenon is well described by Chiarelli et al (2020). As this strain was detected in all seven laboratories on all except one agar plate (Table 5), it is therefore very unlikely that this has influenced the interpretation of the growth on these plates.…”
Section: Discussionsupporting
confidence: 68%
“…These findings highlight the genetic and phenotypic flexibility of K. pneumoniae and its ability to adapt to the dynamic ecosystem within the human body to support prolonged colonization and recurring infections. Studies have shown how K. pneumoniae can evolve in vivo and in vitro within biofilms and exhibit increased antibiotic resistance, as well as the ability for CRKP strains to alter their capsule phenotypes over time, impacting biofilm production ( 51 53 ). Further study into which metabolic pathways and transcriptional changes influenced by carbapenems to significantly induce biofilm production and acquire resistance mutations could shed light on how repeated courses of carbapenem therapy potentially drive long-term persistence of CRKP in the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…More than 77 capsular types (K-types) have been reported in clinical isolates of K. pneumoniae , and recombination events involving the capsule biosynthesis (cps) region are frequently observed within several dominant sequence type (ST) clones, such as CG258 (ST258, ST512, ST11, etc.) isolates ( Wyres et al, 2015 ; Chiarelli et al, 2020 ). In China, ST11 is believed to be the most dominant CRKP clone, with a prevalence greater than 60% ( Zhang et al, 2017 ; Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%